Childbirth experiences of women with a history of physical, sexual, and child abuse: a cross-sectional study of 2,575 Russian women - Anna Suarez; Vera Yakupova (BMC, 2024)
Abstract Background A substantial number of women who subsequently become pregnant and give birth have a history of physical, sexual, and/or child abuse. This study investigated the associations of these types of traumas and their cumulative effect with childbirth experiences, namely, mode of birth, maternal and child complications during pregnancy/childbirth, preterm birth, medical procedures, and obstetric violence during labour. Methods A group of Russian women (n = 2,575) who gave birth within the previous 12 months, completed a web-based survey, where they provided demographic information, details about their childbirth experiences, and a history of trauma. Results Women with any type of past abuse were at higher risk for maternal complications during pregnancy/childbirth (exp(β) < 0.73, p < 0.010 for all). More specific to the type of trauma were associations of physical abuse with caesarean birth, child abuse with complications during pregnancy/childbirth for the baby, and physical and child abuse with obstetric violence (exp(β) < 0.54, p < 0.022 for all). There was a cumulative effect of trauma for all the outcomes except for medical procedures during childbirth and preterm birth. Conclusion This study provides insights into potential different individual effects of physical, sexual, and/or child abuse as well as their cumulative impact on the childbirth experiences. The robust findings about maternal complications during pregnancy/childbirth and obstetric violence highlight the importance of trauma-informed care, supportive policies, and interventions to create safe and empowering birthing environments that prioritise patient autonomy, dignity, and respectful communication.